Potency of testoterone hormone therapy in the Guinea Pig(Cavia porcellus as an Alzheimer's Disease Model - Purwandari Kristianingrum, Yuli; Handharyani, Ekowati; Sajuthi, Dondin; Sulistiawati, Erni (Fakultas Kedokteran Hewan Institut Pertanian Bogor, 2014)
Alzheimer's disease (AD) is an irreversible disease, and is characterized by loss of memory and cognitive progressive. Steroid hormones are hormones that regulate the potential of living nerve cells in the central nervous system (CNS) of normal development to nerve damage. There is no definitive therapy or treatment in patients with Alzheimer's until now. Treatment is only intended to reduce the symptoms caused by Alzheimer's disease. It is very possible that testosterone is a strategic step in addressing neurodegenerative disorders such as Alzheimer's disease [1]. Testosterone and its active metabolite dihydrotestosterone (DHT) has important actions on the brain. The brain is the most responsive tissue to androgen which induces some important brain functions, such as improving the condition of the body and support the cognitive aspects including behavior [2]. The principle of treatment of Alzheimer's disease is basically reduce and eliminate the production of amyloid β plaques (βA). This study aims to investigate the influence of the hormone testosterone in the guinea pig plasma testosterone levels in the blood plasma and pathological changes in the brain with Hematoxylin & Eosin staining (HE).